PENERAPAN MANAJEMEN BERBASIS SEKOLAH (MBS) DALAM MENINGKATKAN MUTU PENDIDIKAN DI SD NEGERI 124 INPRES MONCONGKOMBA KABUPATEN TAKALAR - Irmawati Thahir; Muhammad Nawir; Amriani (STKIP Subang, 2024)
Implementation of School-Based Management (MBS) in Improving the Quality of Education at Public Elementary School 124 Moncongkomba Inpres, Takalar Regency. Currently, the implementation of education in Indonesia is still far from effective. Where education in Indonesia is less able to produce graduates who have the expected quality of human resources. Implementing school-based management requires understanding and commitment from all parties, namely the implementation of education to related parties. The problem in this research is how to implement school-based management (MBS) in improving the quality of education at SD Negeri 124 Inpres Moncongkomba, Takalar Regency. Currently, the implementation of education in Indonesia is still far from effective. Where education in Indonesia is less able to produce graduates who have the expected quality of human resources. Implementing school-based management requires understanding and commitment from all parties, namely the implementation of education to related parties. The problem in this research is how is the implementation of school-based management on the seven pillars at SD Nelgelri 124 Inprels Moncongkomba, Takalar Regency? This research aims to find out how School-Based Management is implemented in improving the quality of education at SD Negeri 124 Inprels Moncongkomba. The type of research used is qualitative research carried out using the case study method. The results of research on the implementation of school-based management at SD Negeri 124 Inpres Moncongkomba are that there is a need to implement School-Based Management at SD Negeri 124 Inpres Moncongkomba because this school is serious about improving the quality of education, by improving school governance better so that the goals, vision and the school's mission can be realized or achieved. With the implementation of SBM, all parties involved in the school can communicate with each other to improve and maintain the quality of educational services. The implementation of school-based management at SD Negeri 124 Inpres Moncongkomba has seen significant improvements in the seven pillars of education. These indicators can be seen in the increase in interest in learning among students, the progress of planning, organizing, implementing and controlling/evaluating each pillar of education in terms of input, process and output.